O Corpo surdo no discurso humorístico: a LIBRAS como saber-poder - Tobias Oliveira, Silvana (2022)
This paper aims to analyze how the bodies of deaf subjects are captured by linguistic knowledge in humorous discourse and how they produce stigmas in power-knowledge relations. To achieve our purpose, we followed concepts of Foucauldian Discourse Analysis, specifically with regard to theoretical and methodological procedures, as well as authors of Cultural Studies.Au  methodology we focused on the description of the (re) produced enunciates in the video Surdos no Metrô, from the Youtube channel Desconfinados, in order to examine them. To meet our goal, we chose enunciates and frames selected by capture tool, in which we observed the knowledge-power relationship between the deaf humorists present in the humorous scene of the channel Desconfinados. The enunciative scene shows how the Deaf is captured by identitary existence/resistance embodied by the linguistic knowledge of Libras and public welfare and how these pieces of knowledge constitute power relations between the Deaf themselves and hearing subjects who do not know Libras, instilling what is called culture, Deaf identity and inclusion practices in the public/media space.